دراسة حقلية لتأثير النفط المتسرب في بعض العوامل البيئية وتقديرها في المياه - فارس جاسم محمد الامارة; علي مهدي ناصر (University of Thi-Qar Journal of Science, 2019)
A study has been conducted for spilled crude oil in sand reservoir 2x2x1m3 eachcontains 1200 l water from Garmat Ali River, crude oil was poured in each reservoir asfollows: 1.2, 2.4 and 3.6 l in the first three reservoirs respectively while the fourth wasleft without oil as control. The four reservoir were exposed to climate under the sun andwind, the changes in the spilled oil layers were investigated as well as someenvironmental parameters for water underneath which are temperature, salinity anddissolved oxygen. Moreover, petroleum hydrocarbons were measured after certainintervals of 7, 12, 22 and 60 days of exposure. Spilled oil layers reduced with time aspetroleum hydrocarbons dissolved in the water for reservoir with oil in whichconcentrations of dissolved petroleum hydrocarbons increased directly with thickness ofoil spill compared with control reservoir. After a week of exposure dissolved petroleumhydrocarbons measured were 833.96 , 1564.33 and 2031.48 μg/l in the reservoir 1,2 and3 respectively compared with 53.04 μg/l in the control reservoir. These levels weredecreased with time in which they reached to 355.22, 623.65 and 1549.21 μg/l in thereservoirs 2 , 3 and 4 respectively after 60 days of exposure. Results were explained onthe basis of biodegradation, photo-oxidation due to increase temperature and decreasedissolved oxygen accompanied the exposure, in which temperature increased directlywhile dissolved oxygen decreased with exposure time and thickness of spilled oil. Moreover, salinity is increased with time to be 1.57, 2.41, 2.34, 2.49 and 2.61 ‰ duringexposure times 1 hour, 7, 12, 17 and 22 days respectively in the reservoir No. 4. Asthickness of oil slick increased the salinity is increased to become 2.12, 2.22 and 2.61‰in the reservoirs 2 , 3 and 4 respectively after 22 days of exposure to natural conditions